2012
DOI: 10.1002/esp.3348
|View full text |Cite
|
Sign up to set email alerts
|

The impact of stress history on bed structure

Abstract: Recent research has started to focus on how prolonged periods of sub-threshold flows may be capable of imparting structural changes that contribute to increased bed stability. To date, this effect (termed ‘stress history') has been found to be significant in acting to increase a bed's critical shear stress at entrainment threshold. However, it is supported by only limited, qualitative and often speculative information on the mechanisms of this stabilisation process in grade-specific studies. As such, this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(114 citation statements)
references
References 30 publications
7
102
5
Order By: Relevance
“…Laser scans have very high accuracy (± 0.1-0.2 mm) (e.g., Marion et al, 2003;Ockelford and Haynes, 2013) but are only realistic during dry bed conditions before and after flume runs. Detailed bed topography can be used to characterize bed roughness instead of relying on a representative grain size as is commonly done in the field.…”
Section: Bed Topography and Grain Size Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser scans have very high accuracy (± 0.1-0.2 mm) (e.g., Marion et al, 2003;Ockelford and Haynes, 2013) but are only realistic during dry bed conditions before and after flume runs. Detailed bed topography can be used to characterize bed roughness instead of relying on a representative grain size as is commonly done in the field.…”
Section: Bed Topography and Grain Size Distributionsmentioning
confidence: 99%
“…In addition, even for a constant bed grain size distribution, different sequences of applied shear stresses can influence the bed grain arrangement. The onset of motion may therefore vary through time depending on the flow history of a given bed (Haynes and Pender, 2007;Mao, 2012;Ockelford and Haynes, 2013).…”
Section: Grain Scale Transport Mechanicsmentioning
confidence: 99%
“…Other bed state controls include the degree of overlap, interlocking and imbrication among grains, and bed compaction or dilation (e.g., Parker, 1990;Wilcock and Crowe, 2003;Sanguinito and Johnson, 2012;Buscombe and Conley, 2012;Mao, 2012;Kirchner et al, 1990;Marquis and Roy, 2012;Powell and Ashworth, 1995;Richards and Clifford, 1991;Ockelford and Haynes, 2013). By combining experimental data and a numerical model, Measures and Tait (2008) show that increasing grain-scale bed roughness tends to shelter downstream grains, reducing entrainment.…”
Section: Previous Work: Mechanistic Controls On τ * Cmentioning
confidence: 99%
“…Flow characteristics influencing τ * c include particle Reynolds number, flow depth relative to grain size, the intensity of turbulence, the history of prior flow both above and below transport thresholds, and the partitioning of stress into form drag and skin friction (e.g., Shvidchenko and Pender, 2000;Ockelford and Haynes, 2013;Schneider et al, 2015;Valyrakis et al, 2010;Celik et al, 2010). Most flowdependent controls are not independent of the bed surface controls.…”
Section: Previous Work: Mechanistic Controls On τ * Cmentioning
confidence: 99%
“…Bombar et al (2011) reported an anti-clockwise hysteresis in experiments with a static armour layer, where the maximum bedload transport was possible only after the peak flowrate, when the armour layer was destroyed by a high flow. When sediment is heterogeneous, sediment transport is affected by grain arrangement (Ockelford and Haynes, 2013): microforms (clusters) are formed (Mao, 2012), static or mobile armour layer appears (Guney et al, 2013), and partial transport may take place (Sun et al, 2015). To make things more complicated, bedload transport is additionally controlled by the availability of upstream sediment in supply-limited rivers (Mao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%